Enforced Disappearance in Colombian Public Scene: Social Mobilization and Visibility Strategies (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
In Colombia, national legislation acknowledges forced disappearance as a crime against humanity. However, at the public level it has little visibility, if at all. In this paper, we seek to reflect upon the strategies of representation in relation to the missing bodies of those disappeared, as well as to analyze how social mobilization efforts have been constructed in order to evoke their memory in the public sphere and promote forced disappearance as a contemporary crime. Looking at the work done by actors that pursue the visibilization of forced disappearance in the city of Bogotá, we analyze the artistic and cultural forms used to both display the bodies of the disappeared and bear witness to impunity as a widely used practice in Colombia. In other words, we inquire about the ways in which the idea of visibility regarding violence is culturally constructed and disseminated throughout Colombia.
Keywords: Forced Disappearance; Social Mobilization; Representational Strategies; Colombia.